An evaluation of the effect of an educational intervention for Australian social workers on competence in delivering brief cognitive behavioural strategies: A randomised controlled trial - Moulding R; Bland R; Joubert L; Blashki G; Armstrong G; Gunn J; Naccarella L (BMC, 2010)
Abstract Background Broad community access to high quality evidence-based primary mental health care is an ongoing challenge around the world. In Australia one approach has been to broaden access to care by funding psychologists and other allied health care professionals to deliver brief psychological treatments to general practitioners' patients. To date, there has been a scarcity of studies assessing the efficacy of social worker delivered psychological strategies. This study aims to build the evidence base by evaluating the impact of a brief educational intervention on social workers' competence in delivering cognitive behavioural strategies (strategies derived from cognitive behavioural therapy). Methods A randomised controlled trial design was undertaken with baseline and one-week follow-up measurement of both objective and self-perceived competence. Simulated consultations with standardised depressed patients were recorded on videotape and objective competence was assessed by blinded reviewers using the Cognitive Therapy Scale. Questionnaires completed by participants were used to measure self-perceived competence. The training intervention was a 15 hour face-to-face course involving presentations, video example consultations, written materials and rehearsal of skills in pairs. Results 40 Melbourne-based (Australia) social workers enrolled and were randomised and 9 of these withdrew from the study before the pre training simulated consultation. 30 of the remaining 31 social workers (97%) completed all phases of the intervention and evaluation protocol (16 from intervention and 14 from control group). The intervention group showed significantly greater improvements than the control group in objective competence (mean improvement of 14.2 (7.38-21.02) on the 66 point Cognitive Therapy Scale) and in subjective confidence (mean improvement of 1.28 (0.84-1.72) on a 5 point Likert scale). On average, the intervention group improved from below to above the base competency threshold on the Cognitive Therapy Scale whilst the control group remained below. Conclusions Social workers can attain significant improvements in competency in delivering cognitive behavioural strategies from undertaking brief face to face training. This is relevant in the context of health reforms that involve social worker delivery of evidence based psychological care. Further research is required to assess how these improvements in competence translate into performance in practice and clinical outcomes for patients.